Mechanisms and management of CAR T toxicity - Ferreri, Christopher J.; Bhutani, Manisha (Frontiers in Oncology, 2024)
Chimeric antigen receptor (CAR) T cell therapies have dramatically improved treatment outcomes for patients with relapsed or refractory B-cell acute lymphoblastic leukemia, large B-cell lymphoma, follicular lymphoma, mantle cell lymphoma, and multiple myeloma. Despite unprecedented efficacy, treatment with CAR T cell therapies can cause a multitude of adverse effects which require monitoring and management at specialized centers and contribute to morbidity and non-relapse mortality. Such toxicities include cytokine release syndrome, immune effector cell-associated neurotoxicity syndrome, neurotoxicity distinct from ICANS, immune effector cell-associated hemophagocytic lymphohistiocytosislike syndrome, and immune effector cell-associated hematotoxicity that can lead to prolonged cytopenias and infectious complications. This review will discuss the current understanding of the underlying pathophysiologic mechanisms and provide guidelines for the grading and management of such toxicities.